Comparative Population Studies at Fifty: Views on the Past, Present, and Future - Trappe, Heike; Rau, Roland; Schiefer, Katrin; Spieß, C. Katharina (Comparative population studies, 2025)
The 50th volume of Comparative Population Studies (CPoS) is a significant milestone in the journal’s history, offering us the opportunity to reflect on its development into a key platform for population research, major achievements, and future aspirations. Besides a retrospective, we present a forward-looking perspective, outlining our vision for the journal’s trajectory in an ever-changing scientific landscape. Furthermore, we offer insights from 50 years of CPoS, including the total number of submissions, the geographic origins of our authors, and an analysis of the journal’s most downloaded articles. This editorial is the first in a series accompanying CPoS volume 50 in our anniversary year. Further editorials by former CPoS editors, publishers, and authors will follow, giving an overview of the editorial processes, guiding principles, and strategic considerations that have and will continue to shape the journal’s identity and impact. * This article belongs to a series celebrating the journal's 50th anniversary.